Personal and social responsibility development: exploring the perceptions of Portuguese Youth football coaches within competitive youth sport - Santos, Fernando (2018)
Youth sport is a valuable context to foster the development of personal and social responsibility (PSR). Within competitive youth sport coaches face many challenges promoting PSR while still being required to win. However, information related to the role played by coaches in PSR development within competitive youth sport is scarce and thus additional research is required. The purpose of this study was to analyse the perceptions of youth coaches on delivering, and barriers to delivering PSR in competitive youth sport. The data were collected through semi-structured interviews conducted with 17 youth coaches who coached under-15 football teams in Portugal. A thematic analysis was performed which generated high (e.g. coaching practice) and low order categories (e.g. positive transference). The findings showed that coaches considered PSR development important in different developmental stages. The relationship between parents and coaches was identified as a key factor. Coaches experienced constraints to their intervention towards PSR development, such as challenging athlete behaviours which were resolved by implementing negative teaching strategies. Coaches also mentioned a low number of strategies to foster transference of PSR to other life domains.